Long-term outcome of subretinal coapplication of rtPA and bevacizumab followed by repeated intravitreal anti-VEGF injections for neovascular AMD with submacular haemorrhage. Issue 5 (15th December 2011) - Treumer, Felix; Roider, Johann; Hillenkamp, Jost
Abstract : Aim: To evaluate short-term and long-term outcomes of subretinal coapplication of recombinant tissue plasminogen activator (rtPA) and bevacizumab followed by intravitreal injections of bevacizumab or ranibizumab for neovascular age-related macular degeneration with submacular haemorrhage (SMH). Methods: Retrospective, consecutive, interventional case series of 41 eyes of 40 patients. All patients underwent pars plana vitrectomy with subretinal coapplication of rtPA and bevacizumab and intravitreal gas tamponade. Postoperatively, repeated intravitreal injections of bevacizumab or ranibizumab were applied following a flexible, predominantly visual acuity-driven re-treatment regimen. Results: Mean diameter of SMH was 4.5 disc diameters (range 1.5–12). Complete displacement of SMH was achieved in 35 of 41 eyes. Large and prominent SMH extending beyond the vascular arcades were completely displaced in six of eight eyes. SMH recurred in eight eyes after a mean of 9.1 months (2–19). A mean of 4.5 (2–9) intravitreal anti-vascular endothelial growth factor injections were applied during 12 months postoperatively. Short-term (3 months, n=41), mean best corrected logMAR visual acuity (BCVA) improved significantly from the preoperative value 1.7 (3.0–0.5) to 0.8 (1.6–0.2). 12 eyes had reading ability (≤logMAR 0.4) and 29 eyes had gained ambulatory visual acuity (≤logMAR 1.6). Long-term (mean 17 months (12–32), n=26) BCVA was 0.9 (1.6–0.1). Compared with short-term, BCVA had decreased in 12 of 26 eyes. Conclusion: The operation effectively displaces small and large SMHs. In the long-term, a predominantly visual acuity-driven re-treatment regimen puts the initial functional improvement at risk. More sensitive re-treatment parameters may help to improve long-term functional outcome.